The Role of a Good Quality Autopsy in Pediatric Malpractice Claim: A Case Report of an Unexpected Death in an Undiagnosed Thymoma - Di Nunno, Nunzio; Patanè, Federico Giuseppe; Amico, Francesco; Asmundo, Alessio; Pomara, Cristoforo (Frontiers in Pediatrics, 2020)
Thymomas are extremely rare in the first 20 years of life, with different clinical presentations: from asymptomatic mediastinal masses to compressive and paraneoplastic syndromes. In pediatric population the respiratory disorders have a higher incidence. The overall thymoma mortality rate is described as 40% and metastasized tumors are more aggressive. This case report describes a compressive syndrome caused by a thymoma in which symptoms were exacerbated by a concurrent pulmonary infection, thus leading an affected infant to sudden death despite medical treatment. In this case, patient's death occurred just before the differential diagnostic process got completed. Malpractice claim was based on the missing diagnosis as well as the suspect of inadequate provided care. Consequently, autopsy played a crucial post-mortem role to find out the cause of death, and to exclude any professional liability. Despite modern diagnostic techniques, autopsies are still the best available forensic tool. It is useful to remember that death is a fact of life, therefore not always preventable.